Animations driving uptake of socio-technical innovations by women farmers - Puskur, Ranjitha; Nchanji, Eileen; Cosmas, Lutomia; Ketema, Dessalegn; Muteti, Thomas; Gartaula, Hom; Mukhopadhyay, Prama; Mapedza, Everisto D.; Chadha, Deepali (CGIAR System Organization, 2024)
Animations and online visual presentations dedicated to teaching and reflections on the uptake of socio-technical innovations by women farmers.